Caffeine increases performance in cross-country double-poling time trial exercise - Stadheim, H. K.; Kvamme, B.; Olsen, R.; Drevon, C. A.; Ivy, J. L.; Jensen, J. (Medicine & Science in Sports & Exercise, 2013)
Purpose: Caffeine (CAF) improves performance in both short- and long-duration running and cycling where performance relies on power output and endurance capacity of leg muscles. No studies have so far tested the effects of CAF while using the double-poling (DP) technique in cross-country skiing. When using the DP technique, arm muscles provide the speed-generating force and therefore play an important role in performance outcome. The metabolism of arm muscles differs from that of leg muscles. Thus, results from studies on leg muscles and CAF may not be directly applicable to exercises while using the DP technique in cross-country skiing. The purpose of our study was therefore to investigate the effects of CAF on exercise performance in DP. Method: Ten highly trained male cross-country skiers (VO2max running, 69.3 ± 1.0 mL/kg/min) performed a placebo (PLA) and CAF trial using a randomized, double-blind, crossover design. Performance was assessed by measuring the time to complete an 8-km cross-country DP performance test (C-PT). CAF (6 mg/kg) or PLA was ingested 75 min before the C-PT. Results: CAF ingestion reduced the time to complete the 8-km C-PT from 34:26 ± 1:25 to 33:01 ± 1:24 min (P < 0.05). The subjects maintained higher speed and HR throughout the C-PT, and lactate was higher immediately after the C-PT with CAF exposure compared with PLA. Subjects reported lower RPE at submaximal intensities during CAF compared with PLA, although HR was similar. Conclusion: CAF intake enhances endurance performance in an 8-km C-PT, where arm muscles limit performance. CAF ingestion allowed the participants to exercise with a higher HR and work intensity possibly by reducing perception of effort or facilitating motor unit recruitment.